Unveiling van Hove singularity modulation and fluctuated charge order in kagome superconductor CsV_{3}Sb_{5} via time-resolved ARPES - Yigui Zhong; Takeshi Suzuki; Hongxiong Liu; Kecheng Liu; Zhengwei Nie; Youguo Shi; Sheng Meng; Baiqing Lv; Hong Ding; Teruto Kanai; Jiro Itatani; Shik Shin; et al. (Physical Review Research)
Kagome superconductor CsV_{3}Sb_{5}, which exhibits intertwined unconventional charge-density wave (CDW) and superconductivity, has garnered significant attention recently. Despite extensive static studies, the nature of these exotic electronic orders remains elusive. In this study, we investigate the nonequilibrium electronic structure of CsV_{3}Sb_{5} via time- and angle-resolved photoemission spectroscopy (ARPES). Our results reveal that upon laser excitation, the van Hove singularities immediately shift towards the Fermi level and subsequently oscillate in sync with a 1.3-THz coherent phonon mode. By analyzing the coherent intensity oscillations in the energy-momentum (E-k) map, we find that this coherent phonon is strongly coupled with electronic bands from both Sb and V orbitals. While typically observable only in the CDW state, remarkably, we find that the 1.3-THz coherent phonon mode can be persistently excited at temperatures above T_{CDW}, suggesting the potential existence of fluctuated CDW in CsV_{3}Sb_{5}. These findings enhance our understanding of the unconventional CDW in CsV_{3}Sb_{5} and provide insights into the ultrafast control of kagome superconductivity.